MEKANISME DAN TAKTIK BERTAHAN: PENOLAKAN REALITA DALAM KONSELING - Sigit Sanyata (Paradigma, 2009)
Individual mechanism to avoid reality is represented by the weakness in seeing themselves objectively. Avoiding behavior is discussed in two part :defense mechanism and defense tactic. Defense mechanism meaning as unconscious behavior coming out from a person to fulfilling his needs, or behavior that avoid (not accept) something he doesn’t want. Defense tactic has the same concept with defense mechanism but different on the source. The important thing is the counselee should not make a self defense. It can be done by an effective communication between the counselor and counselee. The counselor ability in counseling basic skill will be a preventive way that avoid the counselee in defense mechanism and tactic .Keywords : defense mechanism, defense tactics